System Level Study of LTE-Advanced Multiple Antenna System with Inter-Band Carrier Aggregation - Abdalla, Dana Salahalddin; Mohammed, Salim Qadir (Kurdistan Journal of Applied Research, 2018)
Spatial Multiplexing (SM) multiple antenna systems and Carrier Aggregation (CA) are techniques introduced in Long Term Evolution- Advanced (LTE?Advanced) to support high data rates by increasing the number of transmission paths and the available bandwidth respectively. Therefore, in this study we evaluate the performance of LTE-Advanced physical downlink shared channel for single and SM multiple antenna systems in two different frequency bands. The radio channel is modelled using an enhanced Three-Dimensional (3D) international telecommunication union-radio communication sector channel model integrated with base station and user mobile 3D antenna patterns. Except the total received power, similar channel statistics are observed for both frequency bands. The study is performed considering 1x1, 2x2, 4x4 antenna systems in a macro-cell urban environment at Component Carries (CC) of 2600 MHz and 800 MHz to model bands 7 and 20 of CA_7-20 respectively. The performance is evaluated in terms of throughput and SM gain for many base stations and user positions considering various modulation and coding schemes. We used the computationally efficient received bit information rate algorithm to compute the throughput as a function of channel structure and signal to noise ratio. As expected higher throughput is observed for the 800 MHz band over the 2600 MHz band. This is due to the higher total received power of the 800 MHz band. The novel SM gain results show that the SM gain depends on the operating band and it’s less than the number of spatial links. Moreover, the efficiency of inter-band CA in increasing the data rates is a function cell radius and the number of spatial streams.